Respuesta :

Answer:

[tex]\left[\begin{array}{ccc}y=x&y=\frac{2}{3}x&y=\frac{2}{3}x +1 \\-6&-4&-3\\-3&-2&-1\\0&0&1\\3&2&3\\6&4&5\end{array}\right][/tex]

Step-by-step explanation:

-6: y = -6

y = [tex]\frac{2}{3}[/tex] (-6)

y = -4

y = [tex]\frac{2}{3}[/tex] (-6) + 1

y = -4 + 1

y = -3

-3: y = -3

y =  [tex]\frac{2}{3}[/tex] (-3)

y = -2

y =  [tex]\frac{2}{3}[/tex] (-3) + 1

y = -2 + 1

y = -1

0: y = 0

y =  [tex]\frac{2}{3}[/tex] (0)

y = 0

y =  [tex]\frac{2}{3}[/tex] (0) + 1

y = 1

3: y = 3

y =  [tex]\frac{2}{3}[/tex] (3)

y = 2

y =  [tex]\frac{2}{3}[/tex] (3) + 1

y = 2 + 1

y = 3

6: y = 6

y =  [tex]\frac{2}{3}[/tex] (6)

y = 4

y =  [tex]\frac{2}{3}[/tex] (6) + 1

y = 4 + 1

y = 5